Sustainable Business Processes, Market Intelligence, and Food Waste Reduction in Hospitality - Claudia, Vanessa; Permana, Dudi (Dinasti International Journal of Management Science, 2026)
This study develops a conceptual framework explaining how sustainable business processes and market intelligence contribute to food waste reduction through the mediating role of environmental awareness in the hospitality industry. The study adopts a conceptual approach by synthesizing recent literature on sustainability management, strategic capability, and organizational behavior. The proposed framework suggests that sustainable business processes and market intelligence enhance organizational environmental awareness, which subsequently encourages more systematic and effective food waste reduction practices. Environmental awareness is positioned as a central cognitive mechanism linking strategic capabilities with sustainability outcomes. This study contributes theoretically by integrating process-based, market-based, and cognition-based perspectives within a unified structure and provides a foundation for future empirical research and managerial decision-making in hospitality organizations.